Drama/theatre/performance - Shepherd, Simon (The new critical idiom., 2004)
This book examines the history and use of the terms 'Drama', 'theatre' and performance' and investigates the different philosophies, politics, languages and institutions with which they are associated. Analyse attitudes to drama, theatre and performance at different historical junctures. xplore and contextualise the institutionalisation of drama as a university subject, then the emergence of performance' as practice, theory and academic discipline. Discuss crucial terms such as action, alienation, catharsis, character, empathy, interculturalism, mimesis, presence or representation in a substantial 'keywords' section